Pemetaan Data Kriminalitas di Kecamatan Limbur Lubuk Mingkuang Kabupaten Muaro Bungo Berbasis WebGIS - Illahi, Manisa Rahmi; Yulfa, Arie (Lembaga Yasin AlSys, 2024)
Crime is a big problem that is always present and difficult to avoid. Of course, there are several villages that are classified as prone to crime and the public needs to increase awareness, however, there is limited information. Based on these problems, research was carried out with the aim of: 1. Knowing the forms of crime that occur in Limbur Lubuk Mengkuang District. 2. Providing web-based information services on crime maps in Limbur Lubuk Mingkuang District, Muaro Bungo Regency.This type of research is quantitative. Data is processed using a prototype model to collect data or information regarding system requirements. at the system evaluation stage using Usability Testing with the SUS (System Usability Scale) This research produces a WebGIS with 4 main menus, namely homepage, login, map and crime information.